2023
DOI: 10.1200/jco.2023.41.4_suppl.301
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between FGFR2 immunohistochemistry assays and fluorescence in situ hybridization (FISH) in metastatic gastric cancer: A comparison study.

Abstract: 301 Background: FGFR2 status of a patient with metastatic gastric adenocarcinoma could be an important factor in determining optimal treatment strategy with FGFR2 inhibitors and antibodies. The question remains how well different assays agree on the FGFR2 status of the same patient and whether one test can be substituted by another. Methods: Pairwise comparison of 4 tests based on the same patient population was performed: 3 IHC assays [Abcam clone EPR24075-418, R&D clone 98706, Santa Cruz clone C-8] and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It is already known that HER2 and PD-L1 heterogeneity encompasses not only interpatient variability (intertumor heterogeneity), but also variations within the same tumor (intratumor heterogeneity) [10][11][12]. In a retrospective study, we evaluated 109 patients with locally advanced or metastatic gastric adenocarcinoma [13]. Overall, FGFR2 expression was detected in 43% cases and amplification in 8% cases [14].…”
Section: Challenges Of Fgfr2 Testing In Metastatic Gastric Adenocarci...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is already known that HER2 and PD-L1 heterogeneity encompasses not only interpatient variability (intertumor heterogeneity), but also variations within the same tumor (intratumor heterogeneity) [10][11][12]. In a retrospective study, we evaluated 109 patients with locally advanced or metastatic gastric adenocarcinoma [13]. Overall, FGFR2 expression was detected in 43% cases and amplification in 8% cases [14].…”
Section: Challenges Of Fgfr2 Testing In Metastatic Gastric Adenocarci...mentioning
confidence: 99%
“…Immunohistochemical FGFR2 expression proved to be a more clinically relevant than amplification. Other study also showed that fluorescence in situ hybridization should not be recommended as a substitute for a FGFR2 immunohistochemistry assay due to the high probability of false negative prediction as a result of intratumor heterogeneity and low Pearson correlation coefficients [ 13 ].…”
Section: Challenges Of Fgfr2 Testing In Metastatic Gastric Adenocarci...mentioning
confidence: 99%